A New Insight Into Toxicity of Database Compounds from Ginger (Zingiber officinale) by Modelling Study - Frimayanti, Neni; Febrina, Mira; Yuri Amalia, Annisa (Universitas Andalas, 2024)
Dengue haemorrhagic fever (DHF) is an infectious disease caused by the dengue virus. The dengue virus is transmitted through female mosquitoes, especially Aedes aegypti and Aedes albopictus. Indonesia is a dengue endemic country, and almost all provinces in Indonesia are infected with dengue. However, targeted antiviral drugs against dengue virus (DENV) are not yet available. This study aimed to determine the potential of three compounds isolated from ginger (Zingiber officinale) as dengue NS2B/NS3 inhibitors, and to predict the physicochemical properties (drug-likeness) and potential toxicity of drug candidates. Ginger isolates in the form of [8]-gingerol, [6]-paradol, shogaol were obtained from the Natural Discovery Database (NADI). Toxicity and drug-likeness predictions were performed using ProTox-II and SwissADME, and Molecular Operating Environment (MOE) 2022.0901 was used for the molecular docking process. Results: The results showed that the ginger compound (Zingiber officinale), [8]-Gingerol, [6]-Paradol, and Shogaol, had binding free energy of -7.18, -7.10 and -6.88 kcal/mol, respectively. It is indicated that three compounds had potentiality to inhibit the NS2B/NS3 protein complex with a binding free energy that was almost equivalent to that of the positive control, panduratin A, and similar to that of the positive control, which can be seen in superimposition. In addition, three compounds isolated from ginger met the drug-likeness parameters. Based on the analysis of in silico toxicity studies, the three compounds isolated from ginger showed different levels of toxicity. Therefore, based on the safety level of oral use, the [8]-gingerol compound is safer to develop as a dengue antiviral drug, where the LD50 value of [8]-gingerol is 2.580 mg/kg with a class V toxicity level that is practically nontoxic.